Investigating the professional identity and resilience in nursing students during the COVID-19 pandemic - Seyedeh Roghayeh Jafarianamiri; Mojtaba Qanbari Qalehsari; Ali Zabihi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Professional identity includes the values and beliefs of a nurse that guide her thinking, action, and interaction with patients. The stressful conditions of the COVID-19 pandemic may have affected nursing students' resilience and attitudes toward their profession. Therefore, the aim of this study was to investigate the professional identity and resilience in nursing students during the COVID-19 pandemic. MATERIALS AND METHODS: This cross-sectional descriptive study was performed in November and December 2020 with the participation of all nursing students of Babol University of Medical Sciences who spent at least one semester of internship in a hospital during the COVID-19 pandemic. Data were collected using demographic questionnaire, Connor-Davidson resilience scale, and nursing students' professional identity scale. Data analysis was performed using independent t-test, ANOVA, and correlation tests at a significance level of 0.05. RESULTS: Nursing students in the 3rd, 5th, and 7th semesters have spent a minimum of 13 and a maximum of 151 days of internship during the pandemic period. The mean score of professional identity of nursing students was 61.86 ± 9.34 and their mean resilience score was 32.08 ± 13.54. The resilience score of 92% of students was below 50. Professional identity was significantly stronger, and resilience was considerably higher in students who were satisfied with their profession and lived with their families (P < 0.05). In other words, students with higher professional identity scores had higher resilience (r = 0.39, P = 0.000). CONCLUSION: Despite a good professional identity score, the resilience of nursing students during the COVID-19 pandemic is low. Therefore, professors and the clinical education system should provide more support for students in such stressful times as the COVID-19 pandemic period.